If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(t + -3) + 7 = 6t + -9 Reorder the terms: -5(-3 + t) + 7 = 6t + -9 (-3 * -5 + t * -5) + 7 = 6t + -9 (15 + -5t) + 7 = 6t + -9 Reorder the terms: 15 + 7 + -5t = 6t + -9 Combine like terms: 15 + 7 = 22 22 + -5t = 6t + -9 Reorder the terms: 22 + -5t = -9 + 6t Solving 22 + -5t = -9 + 6t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6t' to each side of the equation. 22 + -5t + -6t = -9 + 6t + -6t Combine like terms: -5t + -6t = -11t 22 + -11t = -9 + 6t + -6t Combine like terms: 6t + -6t = 0 22 + -11t = -9 + 0 22 + -11t = -9 Add '-22' to each side of the equation. 22 + -22 + -11t = -9 + -22 Combine like terms: 22 + -22 = 0 0 + -11t = -9 + -22 -11t = -9 + -22 Combine like terms: -9 + -22 = -31 -11t = -31 Divide each side by '-11'. t = 2.818181818 Simplifying t = 2.818181818
| 10+2(x-3)=18 | | (6x+4)10x= | | 60+60+[4x-80]=180 | | 7(x-2)+7x=5(x+4)-7 | | 7x+y=215 | | y-1=0.33(x+3) | | xlogM+2logM-3xLogN+4LogN=0 | | 28.3=-12w | | 3+6x=43-4x | | 0.12x+0.9(x-2)=0.01(2x-3) | | -28=-(r-4)+7(7+4r) | | 41/6=31/3 | | 3x+7-2=2x+6-1 | | 2+5x=65-2x | | 6n=13z | | 30+63+[2x+7]=180 | | k+32=70 | | -2x+6=-3x+10 | | 24-7=10 | | -6-5x=-(-5+6x)-5 | | 8+18c-6= | | 1.63q=9.7 | | 4.2-2y=16.8 | | 14y-8y=24 | | 3x-2y-z=-24 | | 2.5x+3=23 | | (2x+4)2=5x-6 | | -2(z+5)=-10 | | 2x+18=23+8+x | | 1.68+m=14.29 | | 2.7+10m=6.41 | | 4x-2=4(x-1) |